Twin to Twin Transfusion Syndrome - Serudji, Joserizal (Andalas Obstetrics And Gynecology Journal, 2022)
Introduction: Collateral arterial growth is an effective adaptation process to maintain blood supply in myocardial tissue distal to a coronary stenosis and in other vascular beds where feeding arteries are obstructed (1) . The drive for outgrowth and remodelling of arterial collaterals is an increased shear stress due to an enlarged blood flow occurring after the event of stenosis in a near by conduit artery. Remodelling includes increased growth of the diameter and length of the collateral, causing the characteristic tortuous or cork screw appearance (1) .Whilst collateral growth is generally beneficial, we will present evidence that arterial collateral out growth occurred in a monochorionic twin placenta where it jeopardised the pregnancy by causing the twin to twin transfusion syndrome (TTTS).Objective: to report a case of twin-to-twin transfusionCase Report: Reporting a case experienced and taken care in our Clinic Fetomaternal RS. Dr .M. Jamil Hospital. A 34 years old woman, gravida 2, para1, at 31 weeks and 6 days amenorrhea, because her pregnant uterus was too large for gestational Referral to tertiary center followed. At 32 weeks and 2 days amenorrhea biometry indicated estimated fetal weights of 1950 and 1450 g (Hadlock), oligohydramnios and polyhydramnios (amniotic fluid index:23cm. No structural anomaly of the heart was seen. No interventions, one course of corticosteroids were administered for fetal lung maturation. At 33 weeks a slight decrease in heart rate variability of the smaller twin was observed. A Caesarean section under spinal anesthesia was performed. Two girls were delivered of 1585 g and 2135 g and in good condition (Apgar scores 8 and 9 after 1 and 5 min in both girls). The monochorionic diamniotic placenta weighed 740 g. The cord of the recipient was centrally inserted and that of the donor velamentally. Placenta was born monochorion, diamnion.Conclusion: TTTS is caused due to unidirectional deep arteriovenous (AV) anastomoses with the superficial short comings. Hypovolemia, oliguria and oligohydramnion occurs in the donor fetus. Hypervolemia, polyuria and polyhydramnios occurs in the recipient fetus